2019
DOI: 10.1177/2158244019845489
|View full text |Cite
|
Sign up to set email alerts
|

Pride in Education: A Narrative Study of Five Finnish Schoolteachers

Abstract: This narrative inquiry explores how Finnish schoolteachers perceived the emotion of pride as a feature of teaching and learning. The study consists of face-to-face interviews with Finnish schoolteachers between 30 and 62 years of age. The results reveal perceptions of teaching and learning that are shaped by a culture of social equality, modesty, group achievement, and tenacity, that is, Sisu. Although the teachers understand achievement pride as a positive feature of learning, in association with cultural nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…There are cultural rules that must be followed but if the rules are respected, one is free to pursue individual pursuits. Consequently, earlier research conducted by this author in 2019 with Finnish high school teachers revealed that pride is not perceived as an emotion to encourage in school children because it disrupts cultural guidelines such as equality and displaying humility (see Etherington, 2019).…”
Section: Finnish Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are cultural rules that must be followed but if the rules are respected, one is free to pursue individual pursuits. Consequently, earlier research conducted by this author in 2019 with Finnish high school teachers revealed that pride is not perceived as an emotion to encourage in school children because it disrupts cultural guidelines such as equality and displaying humility (see Etherington, 2019).…”
Section: Finnish Educationmentioning
confidence: 99%
“…The assumption leading into this study is that pride is a culturally significant universal emotion and is not given equal importance in all cultures, one of those cultures being Finnish culture. Finland was chosen because educators do not tend to celebrate self-pride (see Etherington, 2019). In diverse classrooms, teachers must be cognizant of such cultural differences if they are to teach to diversity.…”
Section: Introductionmentioning
confidence: 99%
“…In the educational context, very few studies have looked into the effects of pride on teachers and students, or in relation to the specific subjects they teach (for exceptions, see: Etherington, 2019; Jenßen, 2021; Pawłowska, 2020; Ross & Stracke, 2016). However, pride is a core emotion in the classroom and is experienced regularly by both teachers (Carson, 2006) and learners (Ross & Stracke, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adamczewski and M. Obrebska (2018), sisu is used as a keyword approach, which helps to understand Finnish culture (Adamczewski, Obrebska, 2018). According to M. Etherington (2019), the concept of sisu became a Finnish notion for describing the strong Finn, and a culture that displayed determination, grit, bravery, resilience, courage and resoluteness in the face of adversity (Etherington, 2019).…”
Section: The Finnish Sisu Phenomenonmentioning
confidence: 99%
“…Researchers who have studied the cultural characteristics and aspects of the Nordic countries have paid special attention to the original phenomenon of sisu as a unique Finnish cultural lifestyle, a kind of ideology of life (Hicks, Tokoi, 1959;Goodrick, 1960;Lander, 1991;Aho, 1994;Lucas, 2002;Tramaa, 2007;Dahlgren, Nurmelin, 2007;Brueggeman, 2008;Pankola, Gronska-Turunen, 2010;Sinkkonen, 2013;Lahti, 2014;Amato-Henderson et al, 2014;Velazquez, 2014;Duckworth, 2016;Pantzar, 2018a;2018b;Nylund, 2018;Adamczewski, Obrebska, 2018;Lahti, 2019;Etherington, 2019). Perseverance, determination, fearlessness, extraordinary endurance, resilience, grit, bravery, courage, resoluteness in the face of adversity, and energy are used to explain the concept of sisu.…”
Section: Introductionmentioning
confidence: 99%